Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Bank Papua Cabang Karubaga Kabupaten Tolikara - Wonda, Yorni; Tatimu, Ventje; Walangitan, Olivia F. C. (Productivity, 2022)
This study aims to determine the effect of compensation and work environment on the performance of employees of Bank Papua Karubaga Branch, Tolikara Regency. The Compensation Variable in the Test uses 8 indicators, the Work Environment Variable uses 12 indicators, the Employee Performance Variable uses 10 indicators. The total population is all employees and the sample is taken from the total population, namely 31 samples using the Structural Equation Modeling (SEM) method with Partial Least Square and using SmartPLS 3.0 software. In this study using a quantitative approach, where the formulation of the research problem is to find the effect of compensation on employee performance, the effect of compensation on the work environment and the influence of the work environment on employee performance. From the results of statistical tests, it was found that compensation has a positive and significant effect on employee performance, compensation has a positive and significant effect on the work environment and the work environment has a positive and significant effect on employee performance.